Social Changes Manifested in the Diachronic Changes of Reform-Related Chinese Near Synonyms - Li, Longxing; Wang, Vincent Xian; Huang, Chu-Ren (Chinese Lexical Semantics, 2022)
This paper examines several reform-related Chinese near synonyms in the thousand-year long history of China, comparing them in both diachronic and synchronic dimensions. Through the enquiries of word frequency and usages in diachronic Chinese corpora and historical Chinese language databases, the results reveal the interplay between social realities and language use This study is an initial effort to relating a number of socially and historically significant synonymous words to the thousand-year long history of China through corpus linguistic enquiry.